Implementing quality improvement in tuberculosis programming: Lessons learned from the global HIV response. (December 2019) - Ikeda, Daniel J.; Basenero, Apollo; Murungu, Joseph; Jasmin, Margareth; Inimah, Maureen; Agins, Bruce D.
Abstract: The quality of care and treatment for tuberculosis (TB) is a major barrier in global efforts to end TB as a global health emergency. Despite a growing recognition of the need to measure, assure, and improve quality of TB services, implementation of quality improvement (QI) activities remains limited. Applying principles of systems thinking, continuous measurement, and root cause analysis, QI represents a proven approach for identifying and addressing performance gaps in healthcare delivery, with demonstrated success in low- and middle-income settings in the areas of HIV/AIDS, maternal, newborn, and child health, and infection control, among others. Drawing from lessons learned in the development of QI programming as part of the global response to HIV, we review key enablers to implementation that may assist NTPs in turning aspirations of high-quality service delivery into action. Under the umbrella of a formal quality management (QM) program, NTPs' attention to planning and coordination, commitment to tracking key processes of care, investment in QI capacity building, and integration of TB QI activities within efforts to advance universal health coverage provide a framework to sustainably implement QI activities.